Chapter 5 (effective customer service) : strategies to improve alumni engagement at UiTM Sarawak / Nur Asfa Arissa Abdul Mutalif - Abdul Mutalif, Nur Asfa Arissa (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Alumni engagement plays a crucial role in the success and reputation of any educational institution. Universiti Teknologi MARA (UITM) Sarawak recognizes the significance of nurturing a strong and active alumni network. By fostering meaningful connections with alumni, the university can leverage their expertise, build collaborations, and enhance its overall standing. Establishing clear and consistent communication channels is essential for effective alumni engagement. UITM Sarawak can utilize various platforms such as social media, email newsletters, and an alumni website to provide updates on university initiatives, events, and achievements. Regular communication ensures alumni stay connected with the institution and encourages their active participation.